PENGARUH LATIHAN UPHILL DAN DOWNHILL RUNNING TERHADAP POWER TUNGKAI SISWA SSB ARTAJUSI LAMPUNG UTARA - Muhammad Yopan Antono; Reza Adhi Nugroho (Universitas Teknokrat Indonesia, 2022)
This study aims to determine the effect of Uphill and Downhill Running exercises on the leg power of SSB Artajusi North Lampung students.This study uses an experimental method with a